Assessment of genetically modified oilseed rape 73496 for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2012‐109). (17th June 2021) - ,; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Oilseed rape 73496 was developed to confer tolerance to the herbicidal active substance glyphosate through the expression of the glyphosate acetyltransferase protein GAT4621. The molecular characterisation data and bioinformatic analyses identify no issues requiring food/feed safety assessment. None of the identified differences between oilseed rape 73496 and its conventional counterpart in the agronomic/phenotypic endpoints tested needs further assessment. Differences identified in seed composition of oilseed rape 73496 as compared to its conventional counterpart raise no safety and nutritional concerns in the context of the scope of this application. No safety concerns are identified regarding toxicity and allergenicity of the GAT4621 protein as expressed in oilseed rape 73496. No evidence is found that the genetic modification would change the overall allergenicity of oilseed rape 73496. Based on the outcome of the comparative and nutritional assessments, the consumption of oilseed rape 73496 does not represent any nutritional concern, in the context of the scope of this application. The implementation of a post‐market monitoring plan is recommended to confirm the predicted consumption data and to verify that the conditions of use are those considered during the pre‐market risk assessment. In the case of accidental release of viable oilseed rape 73496 seeds into the environment, oilseed rape 73496 would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of oilseed rape 73496. The GMO Panel concludes that oilseed rape 73496, as described in this application, is as safe as its conventional counterpart and the non‐genetically modified oilseed rape reference varieties tested with respect to potential effects on human and animal health and the environment.